Feature extraction based on variational mode decomposition and support vector machine for natural gas pipeline leakage. (February 2020) - Lu, Jingyi; Yue, Jikang; Jiang, Chunlei; Liang, Hongwei; Zhu, Lijuan
Issues concerning natural gas pipeline leakage are becoming more prominent than ever because of the continuing expansion of natural gas pipeline networks. Although many scholars have extensively investigated generation and detection methods for pipeline leakage acoustic signals, systematic research on the characteristics of leakage and interference signals remains insufficient. Results show that the method based on the RBF kernel function is feasible for pipeline fault diagnosis, yielding 100% sensitivity, 92% specificity, and 96% accuracy.